Regionalisme Isu Lingkungan Asia Tenggara (1997-2000) - Gema Ramadhan Bastari (Department of International Relations, Universitas Andalas, 2016)
Southeast Asia is an ever growing region. Since 1970, the region hasshown a strongperformance in economic growth and it’s still continued even today. However, the strong economic growth of Southeast Asia also lead to serious externalities in a form of environmental degradation. Deforestation and pollution which has been done in one country affected the nearby countries as well, decreasing the air quality in urban area, and creating many cases of economic losses and health issues. At one point, the Southeast Asian countries realized that environmental degradation is a transnational problem which needed a transnational solution. Regionalism, which is facilitated by the Association of Southeast Asian Nations (ASEAN), became the solution they seek. This paper attempts to explain the process of Environmental regionalism that has happened in Southeast Asia from 1977-2000. The paper concludes that the process of environmental regionalism in Southeast Asia is still stucked in the third phase of regionalism. Lacks of mutual identity between ASEAN members prevents environmental regionalism process in Southeast Asia to advance to the fourth phase. However, the paper also shown some probabilities for it to happen in near future. Keyword: ASEAN, Environment, Regionalism, Regionness,